Commentary on "Platelet Studies in Autism Spectrum Disorder Patients and First-Degree Relatives". Issue 1 (December 2016) - Anderson, George; Cook, Edwin
Abstract We comment on the recent report entitled "Platelet Studies in Autism Spectrum Disorder Patients and First-Degree Relatives" [Molecular Autism 2015;6:57]. We find it commendable that the authors have investigated platelet factors potentially involved in the well-replicated observation of platelet hyperserotonemia in autism. However, we believe the results need a fuller discussion in the context of prior studies, think that certain aspects of the interpretation need to be reassessed, and attempt to provide a framework for further research in this area.